(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
One of the complex problems encountered in forensic practice is the death of an individual who has suffered trauma but has an either pre-existing natural disease or where some natural disease has supervened after trauma. In such circumstances, ascertaining the relative role of trauma and disease and their contributions to death may become an acute medico-legal problem. Herein, we report a case of a 65-year-old male who sustained several injuries in a road traffic accident and died at the hospital after 14 days of treatment. The autopsy, histopathological examination, and review of hospital case records revealed a combination of injuries and diseases that could have contributed to his death. This case report discusses the apportionment of the contribution of trauma and/or disease to death and highlights the need to analyse the percentage of the contribution made by the trauma/ disease to the mortality in cases wherein both trauma and disease co-exist.